Blah blah blah : what to do when words don't work - Roam, Dan. (New York : Portfolio/Penguin, 2011)
Outlines effective strategies for preventing vocabulary misuse and overuse, explaining how to apply the author's'vivid thinking' principles to improve learning, share ideas, and overcome specific obstacles to productivity.
The blah-blahmeter -- If I draw, am I dumb?: an introduction to vivid thinking -- The forest and the trees: the seven essentials of a vivid idea.
Includes bibliographical references (p. 337-339) and index.
Keywords: Thought and thinking -- Art; Visual communication; Communication